Respuesta :
The correct answer is: [tex](x+3)^2-4[/tex]
Step-by-step explanation:
Given expression is:
[tex]x^2+6x+5[/tex]
We can combine terms as:
[tex](x^2+6x) + 5[/tex]
Any term that is added to an expression is also subtracted from the expression
[tex][(x)^2 + 2.x.3] +5[/tex]
So,
[tex]2ab = 6x\\2xb = 6x\\b = \frac{6x}{2x}\\b = 3[/tex]
As b = 3 so (b)^2 will be added and subtracted in the expression
[tex][x^2+6x] +5 + (3)^2-(3)^2[/tex]
[tex][(x)^2+6x+ (3)^2] + 5 - (3)^2\\(x+3)^2 + 5 -9\\(x+3)^2-4[/tex]
Hence,
The correct answer is: [tex](x+3)^2-4[/tex]
Keywords: Polynomials, expressions
Learn more about polynomials at:
- brainly.com/question/4054269
- brainly.com/question/4163549
#LearnwithBrainly